Laboratory Scale Production of Lithium Manganese Oxide as Active Material of Lithium-Ion Batteries in Sol-Gel Method Assisted by Local Biomass - Muhammad Ilham Bayquni; Susanto Sigit Rahardi; Elsy Rahimi Chaldun; Bambang Sunendar Purwasasmita (Jurnal Teknologi Bahan dan Barang Teknik, 2020)
Experimental and theoretical studies of the production of lithium manganese oxide (LiMn2O4) using sol-gel method have been carried out on a larger scale than previous studies.  The purpose of this investigation was to observe sample behavior along the synthesis process to be considered in further scale-up production of lithium manganese oxide, based on the sol-gel method. Calcination products were analyzed by TGA and crystalline phase formation analyzed by XRD. LiMn2O4 spinel phase was formed at 600oC. SEM showed some interesting morphology. Xerogel swelling was observed overwhelmingly during drying at 250oC to 300oC. Exothermic occurrence as a source of irregular and unpredictable auto combustion in the calcination process. Both phenomenon were not observed in a xerogel made with a small amount precursor. Therefore, initial mixture adjustment and additional steps were considered for production.